INTEGRATED DOMESTIC WASTE MANAGEMENT IN ACCORDANCE WITH KAMPUNG IKLIM PROGRAM AT WARAKAS VILLAGE, TANJUNG PRIOK JAKARTA UTARA - Nonon Saribanon; Noverita; Bhakti Nur Avianto; Sara Pebrina; Astri Oktavina (Journal of Social Political Sciences, 2023)
Warakas Village is located in Tanjung Priok District, North Jakarta, with a population of 60,122 people and an area of 100.4 Ha. The increase in population and consumption patterns that continue in society can lead to the amount of landfill waste. Stunting toddlers have become a serious concern for the government. The real impact of stunting is that it can reduce intelligence in children, as the next generation of the nation. The Program conducted in the Warakas Village is to add insight and knowledge, as well as improve skills from environmental, economic, and health aspects, especially in the case of stunting by prioritizing integrated waste/garbage management with prospects for creating innovations in the field of feed and fish farming catfish. The Program is implemented using a participatory approach and an adult learning system, both in training by inviting expert speakers and assisting in the application of the knowledge provided. The benefits obtained are increasing the skills of residents in developing the ability to make solid and liquid fertilizers, plant cultivating with hydroponic system, and production of fish feed independently. All of these activities are interrelated, and can become a place/forum for discussion between residents and other stakeholders. In the health sector, this activity is believed to be able to meet the need for animal protein sources, especially in the Stunting Prevention Action activities which prioritize animal protein intake. Lastly, in the environmental field, waste management activities can support environmental quality improvement by reducing waste piles that are disposed of at garbage dump.